Tivantinib for the treatment of hepatocellular carcinoma. (3rd May 2017) - Best, Jan; Schotten, Clemens; Lohmann, Gregor; Gerken, Guido; Dechêne, Alexander
ABSTRACT: Introduction : Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide with a poor prognosis due to late diagnosis in the majority of cases. Physicians are frequently confronted with patients who are not eligible for curative or locoregional treatments any more. In this scenario, the multi-tyrosine kinase inhibitor sorafenib remains the only systemic first-line treatment option providing modest survival benefit compared to placebo with significant but for most patients acceptable adverse effects. Areas covered : Tivantinib was the first antiproliferative agent to be been applied in a phase III trial based on receptor overexpression analyses after disease progression on sorafenib. While phase I and II trials with tivantinib in second line showed encouraging results, a recent press release announced that the METIV-HCC phase III study of tivantinib in HCC did not meet its primary endpoint of improving overall survival. Expert commentary : Evidence for antiangiogenetic therapy inducing tumor hypoxia leading to overexpression of proliferative genes, including cMET, underlines the potential of tivantinib as second-line treatment. However, as the mechanism of action of tivantinib through cMET inhibition has recently been questioned by several groups, identification of alternative proliferative markers or targets is mandatory.